The perceived impact of tourism development by Cretan residents The perceived impact of tourism development by Cretan residents - Andriotis, Konstantinos (My University, 2004)
This paper presents the results of a study of 194 Cretan households that had the aim of exploring the perceived impacts of tourism on four urban communities and associated resident attitudes toward tourism development. In particular, the study assessed the influence of seven variables (city of residence, length of residence, reliance on tourism, age, gender, education, and income) on residents' attitudes and attempted to identify the underlying factors explaining their perceptions. It was found that the two most important discriminators of residents' attitudes were education and reliance on tourism employment and that the most important dimensions to the urban residents of Crete were economic benefits, cultural and infrastructural benefits, and environmental impacts. Based on the findings, this paper discusses the implications of the research and indicates future research priorities.
Keywords: Impacts; Tourism; Urban communities